Stop-motion and knowledge. Educational video-clip such as writing with media experience - Denicolai, Lorenzo (Form@re - Open Journal per la formazione in rete, 2017)
The article presents the experiment of a good practice for the methodological innovation at the primary school. The activity is based on the production of short knowledge audio-visual pills, realized with the stop-motion technique and through the directly involvement of students in all ideation and production steps of the media text. The experiment, that is also oriented to teachers, aims to educate participants to acquire the know-how and needed competences to write with media, according to the logic of an aware use of technologies in daily school and educative contexts. Stop-motion e conoscenza. Video-pillole educative come esperienza di scrittura con i media L’articolo presenta la sperimentazione di una buona pratica per l’innovazione metodologica nella scuola del primo ciclo. L’attività si basa sulla produzione di brevi pillole di conoscenza realizzate con la tecnica dello stop-motion e il coinvolgimento diretto degli studenti in tutte le fasi di ideazione e di produzione del testo mediale. La sperimentazione, che è rivolta anche agli insegnanti, ha inoltre l’obiettivo di educare i partecipanti ad acquisire le conoscenze e le competenze necessarie per scrivere con i media, in una logica di utilizzo consapevole delle tecnologie nella quotidianità scolastica ed educativa.